Penerimaan Masyarakat Jakarta terhadap Citra Polri dalam Lagu "Bayar Bayar Bayar" Karya Band Sukatani - Syahputri, Febriana Indah; Arviani, Heidy (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to examine the public reception of the police image in the song “Bayar Bayar Bayar” by the band Sukatani among Jakarta residents, using Stuart Hall’s encoding-decoding analysis. The song gained public attention for addressing issues of extortion, bribery, and abuse of power often associated with the police’s negative image. This research employs a qualitative method through in-depth interviews with 12 informants from various backgrounds. The analysis reveals two reception positions: dominant-hegemonic and negotiated. In the dominant-hegemonic position, the public fully accepts the song’s message as a reflection of social reality. In the negotiated position, the public acknowledges the existence of extortion practices but rejects generalizing such behavior to the entire institution, attributing it instead to individual misconduct. No oppositional position was found. The findings conclude that “Bayar Bayar Bayar” functions more as a reinforcement and affirmation of the police’s negative image rather than as a creator of a new one. The song reflects public unease while also opening a space for criticism toward the police institution.
Keywords: Reception Analysis; Stuart Hall; Police Image; Social Criticism